Urgensi Penambahan labour attache sebagai upaya pemenuhan Kewajiban Negara atas Perlindungan Hak-Hak Hukum Pekerja Migran Indonesia di Luar Negeri - Akhmad Hefa Jagad Kusuma; Belva Rajendra; Junendyan Haryosatrio Dewandaru Manikingrat; Anang Setiyawan (Fakultas Hukum Universitas Islam Indonesia, 2025)
Indonesian Migrant Workers (PMI) constitute a vital component of the national economy through substantial remittance contributions, while simultaneously representing the nation on the international stage. However, the legal protection of PMI remains a critical challenge, particularly regarding the role of Labour Attachés (Atnaker) as key actors in labor diplomacy. This study examines the role and challenges faced by Atnaker in safeguarding PMI abroad using a normative legal approach and comparative analysis with migrant worker protection systems in the Philippines and Vietnam. The findings reveal that limited personnel, excessive administrative workload, and weak inter-institutional coordination significantly hinder the effectiveness of Atnaker in fulfilling their protective mandate. Furthermore, deficiencies in legal and diplomatic frameworks exacerbate the vulnerability of PMI to exploitation and rights violations. The study underscores the urgent need for institutional strengthening, including increasing the number of Atnaker, expanding their legal authority, and strengthening their diplomatic capacity as strategic measures to ensure an effective state presence in protecting its citizens abroad.